1 maja [ulotka] . May 1. Flier - Regionalny Komitet "Solidarności" Małopolska. (Regionalny Komitet "Solidarności" Małopolska, 1986)
B&w print on white paper. The leaflet invites for alternative celebrations of the May Day. The text explains the meaning of the holiday and appeals to reappropriate it from the authorities through mass participation in the events organized by Solidarity.